Do Ownership Type and Ownership Concentration Affect Liquidity Creation? A Case Study of Commercial Bank in Indonesia - Juwanik Juwanik; Dwi Nastiti Danarsari (International Journal of Economics Development Research (IJEDR), 2024)
The ability to create liquidity is crucial for banks because a lack of liquidity can lead to failure. This study aims to examine the influence of ownership types and ownership concentration on liquidity creation. The study divides bank ownership types into government ownership, bank ownership, institutional ownership, non-financial company ownership, and family ownership. Additionally, ownership concentration is considered as a moderating variable and measured at various levels ranging from 25% to 85%. The research seeks to investigate whether, according to corporate governance theory, ownership concentration affects a bank's decisions in creating liquidity, and whether, according to ownership structure theory, the risk-taking behavior and agency problems of each ownership type differ, thus affecting the bank's ability to create liquidity. The sample for this study comprises 84 Commercial Banks in Indonesia. The analysis employs dynamic panel data regression, covering the period from 2018 to 2022. Based on the research findings, it is discovered that ownership concentration has a significant negative effect on liquidity creation, indicating that liquidity creation is more prevalent among less concentrated banks. Ownership type does have an effect, but not on all ownership types. Institutional ownership has a positive effect on liquidity creation, whereas bank ownership by other banks has a negative effect. Ownership by the state, family, and company does not significantly affect liquidity creation. Ownership concentration affects liquidity creation at levels below 65%, whereas at levels above 75%, there is no significant influence of ownership concentration on liquidity creation. Another finding is that liquidity creation is more prominent in smaller banks compared to larger ones.